Pertanggungjawaban Notaris terhadap Isi Akta Autentik yang tidak Sesuai dengan Fakta - Tri Yuwono; Dhafin Ramadhan Ariyanto; Albertus Agung Hagai Beni Parhualar Sidauruk (Wajah Hukum, 2026)
The purpose of this research is to analyze the forms of liability that can be imposed on a Notary if the contents of a deed they draft are proven to be inconsistent with the actual facts. A Notary's authority to draft authentic deeds is always accompanied by inherent legal liability, even after the Notary retires, as stipulated in Law Number 2 of 2014. In practice, errors in drafting deeds can occur either intentionally or through negligence, ultimately potentially causing losses to the parties. This situation raises questions about the extent of a Notary's liability for such errors. This study uses a normative juridical method with a statute approach. The results indicate that a Notary can be held accountable if proven to have committed an error that causes losses, whether due to negligence or intent, including general, civil, administrative, and criminal liability. If a Notary intentionally drafts, cooperates in the drafting of, or signs a forged deed, the Notary may be subject to criminal sanctions for their involvement in the act of forgery.